KONSEP PENEBUSAN KRISTUS DALAM KOLOSE 2:14 DAN RELEVANSINYA BAGI GEREJA TORAJA JEMAAT SION LESTARI - Alvary Exan Rerung (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2022)
This paper discusses the understanding of the members of the Toraja Church of the Sion Lestari Congregation about the concept of redemption carried out by Jesus Christ. For them, the concept of redemption is difficult to understand because God is Almighty God, so why did Jesus Christ come down to atone for human sins, when God can do everything with His omnipotence? That is why, this paper aims to provide a simple understanding to the congregation about the concept of redemption carried out by Jesus Christ so that their faith will be stronger. The method used is a qualitative method, literature study, and interviews. In addition, the historical grammatical analysis method is also used in Colossians 2:14, to get a simple understanding of the concept of the redemption of Jesus Christ. That is why this paper focuses on background analysis, literary analysis, context analysis, and grammatical and word meaning analysis, in order to get the result that the sin that Jesus Christ wanted to pay for was a debt. That's why no human can pay it off, because all humans have sin. And only Jesus Christ can and is worthy to do so, for He is the only human without sin.